Environmental Issues in Women's Political Campaigns: Legal Advocacy and Sustainable Development in Indonesian Local Politics - Lestari, Puji; Arditama, Erisandi; Amrullah, M. Fikri; Abdul Mutalib, Mimi Hanida; Kamal, Ubaidillah (Indonesian Journal of Environmental Law and Sustainable Development, 2025)
This article studies the incorporation of environmental concerns in the political campaigns of women candidates within the context of local Indonesian politics. The impacts of environmental problems in coast areas such as Semarang, Demak, Pekalongan, Kendeng mountains, and Wadas Purworejo are serious and pose an overwhelming challenge for women's exacerbated socio-domestic duties. The research is conducted by a normative legal approach through using statutory and implementation frameworks focusing on environmental issues concerning women’s political campaigns in Indonesian local politics, employing content analysis of authoritative books, peer-reviewed journals, on legal advocacy and sustainable development. The findings of the study highlight the stark urban-rural divide where urban candidates were more proactive in pushing sustainable development frameworks. In addition, women who managed to penetrate the legislative milieu exhibited different degrees of engagement with environmental policies; those framed as environmentalists tended to have higher proposed regulation rates. The research shows that most women do not, in campaign rhetoric, grasp the growing public discourse on contestation over policy frameworks at multiple levels—national, regional, and local—and legislative governance approaches that integrate ecological issues and sustainability as a central concern at local and global levels. To address these gaps, the authors argue women politicians need women’s targeted capacity building on environmental legislation that could enhance advocacy for sustainable development at the local level.